2013
DOI: 10.1088/1674-4527/13/2/004
|View full text |Cite
|
Sign up to set email alerts
|

An SPH simulation for cooling and self-gravitating protoplanetary disks

Abstract: We investigate the effects of the cooling function in the formation of clumps of protoplanetary disks using two-dimensional smoothed particle hydrodynamic simulations. We use a simple prescription for the cooling rate of the flow, du/dt = −u/τcool, where u and τcool are the internal energy and cooling timescale, respectively. We assume the ratio of local cooling to dynamical timescale, Ωτcool = β, to be a constant and also a function of the local temperature. We found that for the constant β and γ = 5/3, fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, the study on self-gravitating discs has received more attention recently in numerous publications (e.g. Nelson et al 1998Nelson et al , 2000Gammie 2001;Rice et al 2003Rice et al , 2005Pickett and Durisen 2007;Kley and Nelson 2008;Durisen et al 2008;Cossins et al 2010;Faghei 2012Faghei , 2013Kimura and Tsuribe 2012;Zhang et al 2014). Observational evidence has confirmed the existence of selfgravitating accretion discs in AGNs (Greenhill and Gwinn 1997;Lodato and Bertin 2003;Kondratko et al 2005) and in protostellar and protoplanetary discs (Larson 1984;Lin and Pringle 1987;Beltrán et al 2004;Chini et al 2004;Rodríguez et al 2005;Zhou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study on self-gravitating discs has received more attention recently in numerous publications (e.g. Nelson et al 1998Nelson et al , 2000Gammie 2001;Rice et al 2003Rice et al , 2005Pickett and Durisen 2007;Kley and Nelson 2008;Durisen et al 2008;Cossins et al 2010;Faghei 2012Faghei , 2013Kimura and Tsuribe 2012;Zhang et al 2014). Observational evidence has confirmed the existence of selfgravitating accretion discs in AGNs (Greenhill and Gwinn 1997;Lodato and Bertin 2003;Kondratko et al 2005) and in protostellar and protoplanetary discs (Larson 1984;Lin and Pringle 1987;Beltrán et al 2004;Chini et al 2004;Rodríguez et al 2005;Zhou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many simulations have been performed in order to obtain the value of β crit (e.g. Rice et al 2003Rice et al , 2005Cossins et al 2010;Bate 2011, 2012;Faghei 2013Faghei , 2014. The simulations represent the different values for β crit .…”
Section: Introductionmentioning
confidence: 99%
“…The critical cooling timescale has attracted more attention recently in numerous publications (Rice et al 2003(Rice et al , 2005Cossins et al 2010;Meru & Bate 2011a,b;Faghei 2012Faghei , 2013Meru & Bate 2012). For T Tauri disks, Rice et al (2003) found that the fragments can form for a cooling timescale close to t cool = 3Ω −1 .…”
Section: Introductionmentioning
confidence: 99%
“…They mentioned that, although the quadratic term in the SPH artificial viscosity (β sph ) has very small effects on the dissipation of a gravitationally unstable disk, it can be an important parameter for disk fragmentation. Faghei (2013) investigated the effects of the cooling function in formation of clumps in protoplanetary disks through the use of two-dimensional SPH simulations. He assumed the ratio of local cooling to dynamical timescales to be a constant and also a function of the local temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation